Discurso político violento, autoritarismo e envolvimento com política : um estudo experimental - Gonçalves, Clayton Pereira (2017)
Due to the crisis we are experiencing in Brazil, especially political and economic, the political landscape becomes unstable and subject to change. Resulting in questions to democracy, bringing discussions about other political systems, essential element to lead us to a dystopia disguised as a positive utopia. In this sense, we understand that every process of "awareness", for a radical change, begins with discourses. In politics, it is political discourses. However, all dystopia is accompanied by violence, therefore the defense of a dystopia is built from violent political discourses. The purpose of this research was to investigate the influence of what we call "violent political discourse" on the voter's intention to vote and intention to engage with the campaign, trying to analyze the influence an authoritarian profile and the level of political involvement. We adopt as theoretical basis political marketing, violence, authoritarianism, involvement and attitudes of the voter. This, because we understand that it is a marketing technique the use of political discourses as a way to reach the electorate. Also, to explore the concept of violent political discourse we rely on violence. The authoritarian profile of the voter and his political involvement were identified as factors that could influence the intention of voting and intention of engagement with the campaign. Thus, in the theory of authoritarianism, we have identified a correlation between politics and violence. In the literature on political involvement, we find fundamentals that relate the level of voters to their attitudes. Finally, we discuss how voter attitudes and behavior are built, from cognitive psychology and electoral behavior theory. An experiment was applied to a total of 264 undergraduate students at three universities located in the metropolitan region of Rio de Janeiro. The results pointed out a positive relationship between the stimulus "violent political discourse" and the intention to vote and intention to engage in the campaign. It was also confirmed the influence of the authoritarian profile of the voter and his political involvement on the intention to vote and intention to engage with the campaign. In this way, we emphasize that we must debate and seek awareness about the theme in order to avoid that a dystopia be considered a solution to the political and economic problems that we face.